Inquiry of Literature Evidence for Induced Fit of Cytochrome P450 2C9 for Warfarin, Phen- procoumon, Flurbiprofen and Clopidogrel: A Critical Review. Issue 2 (4th July 2018) - , Thomas Scior; Quiroga-Montes, Israel; Kammerer, Bernd
No abstract available